An overview of self-acceptance among homosexual PLHIV in the kariadi peer support group (PSG), Semarang - Aldi Kristianto; Siska Adinda Prabowo Putri; I Rheny Permitasari (Jurnal Psikologi Tabularasa, 2025)
HIV cases in Semarang City have increased annually, with a high prevalence among Men who have Sex with Men (MSM). The dual stigma associated with being both HIV-positive (PLHIV) and homosexual often leads to social sanctions, which in turn elicit negative emotional reactions as a form of grief in response to such stigma. This study aims to explore the self-acceptance process among homosexual PLHIV members of the Kariadi Peer Support Group (PSG) in Semarang, based on the Kübler-Ross grief model. The research employed a qualitative case study approach. The participants were three homosexual men living with HIV, who contracted the virus through same-sex intercourse and were members of the Kariadi Semarang PSG. Data were collected through semi-structured interviews and overt observation. Data analysis was conducted using the interactive model by Miles & Huberman. Data validity was tested through triangulation and verification with significant others. Findings indicate that all three participants went through the stages of denial, bargaining, depression, and acceptance in their journey toward self-acceptance. Only one participant did not go through the anger stage. Each participant had unique strategies and personal approaches in achieving self-acceptance of their HIV status. The implication of this research highlights the importance of openness among PLHIV in order to gain social support, which plays a critical role in facilitating self-acceptance.